A Structural Equation Model on Stress Coping Among Social Workers - Lara, Rhea Amor; Ladroma, Arian Rey; Recapente, Dionalie Jay; Castilla, Elline; Fahit, Joanaros; Dagohoy, Ronel (Journal of Social Work Education and Practice, 2024)
Coping with stress is crucial for social workers, given the demanding nature of their profession. This study examines the impact of emotional intelligence, interpersonal dynamics, and public service motivation on the ability of social workers in Davao Region, Philippines to manage stress. Utilizing Structural Equation Modeling, the research identifies the best-fit model for stress coping strategies among social workers. Data were collected from 300 participants through random sampling, with the analysis revealing high levels of emotional intelligence, particularly in attention to feelings, and significant public service motivation, especially in commitment to public interest. The study finds that while emotional intelligence and public service motivation positively influence stress coping, interpersonal treatment in the workplace has a negative impact. The best-fit model underscores the importance of integrating emotional intelligence and fostering supportive interpersonal relationships to enhance stress management among social workers. These findings suggest that organizational strategies should focus on emotional intelligence development and positive workplace interactions to improve social workers' resilience against stress. Furthermore, these findings can inform policy-making and organizational strategies to create a more supportive work environment, ultimately enhancing the well-being and efficiency of social workers in their roles.
Keywords: Applied Social Science; Social Work; Mental Health; Stress Coping, Social Workers; Structural Equation Modeling; Philippines